PENDUGAAN FAKTOR YANG MEMENGARUHI JUMLAH BUAH PER TANDAN PADA RAMBUTAN (Nephelium lappaceum, L.) - Kuswandi . (Jurnal Agroekoteknologi, 2016)
Rambutan productivity in Indonesia is still low, thus many efforts have been made to increase it. The objective of this research was to estimate the factors related to the number of fruits per cluster on rambutan trees. The research has been conducted in Aripan experimental garden, Indonesian Tropical Fruit Research Institute, Solok in February, 2016. Variable of production in this experiment was the number of fruits per cluster as the dependent variable. The independent variable was used to estimate the factors related to the number of fruit per cluster, consisted of trunk circumference, crown width, the number of leaves, leaf length, leaf width, plant height, the number of fruits per cluster, and the number of bunches per tree. The results showed that a multiple linear regression model consisting of a number of leaves, plant height and number of bunches per tree can explain 70.21% of phenotypic diversity of the number of fruits per cluster.Keywords: Nephelium, Regression, Estimation